Equalizing The Third Gender Health a Lived Experience Phenomenological Study - A Qualitative Approach - Poonguzhali S; Kirubakaran S; Arun Murugan (Medsci Publications, 2023)
Background: The transgender population is a marginalized social group often targeted for mistreatment and discrimination. This study specifically examined the experiences of transgender people across a range of categories such as: education, employment outcomes, health awareness and mental health status. The study aimed to gain an understanding about the respondents' unique experiences of discrimination being transgender and health awareness. Materials and Methods: The research applied descriptive qualitative phenomenology design. The study was conducted at Department of Community Medicine, Government Omandurar Medical College and Hospital, Chennai on Trans genders using in-depth interview with an open-ended question semi structured Questionnaire after obtaining the informed consent among 4 Transgenders till the data saturation happens. The Transcriptions Data were then analyzed using the Colaizzi method. Results: Marginalized socially and economically, Family and peer rejections, Lack of Job opportunities, Continuous rejection and omission leads to Begging and Active Night life (Survival Sex). Health Care Professionals has less knowledge about the transgender health, sex affirmation surgery is still least preferred among doctors. NGOs roles are very significant in their quality of life, Periodic medical examination including HIV. Conclusion: Transgender's and the word are to be transformed as Third Gender. The Social acceptance from the public will do wonders in their life.